Pengaruh Kesulitan Mencari Kerja Terhadap Pilihan Generasi Muda Untuk Berwirausaha - Jovita, Agnes; Anfasya, Yulindar Fahri; Nia Nurlita; Mustafidan, Ahmad Azka Nur (Universitas Pamulang, 2024)
This study is used to determine whether there is a significant influencebetween difficulty in finding a job and the choice of entrepreneurship among theyounger generation. This research uses a survey with a questionnaire method.Respondents in this study focused on people aged between 18 and 25 years old. Thenumber of respondents obtained was 32 people. In the questionnaire distributed,there were three different questions. These questions are relevant to the purpose ofthe analysis that the researchers conducted. In the current study, it was found thatdifficulty in finding a job influences young people's choice of entrepreneurship.There is also a link between the availability of capital and the sustainability of anentrepreneurship.Keywords: Entrepreneurship, difficulty finding a job, capital